Preparation method of polyester loose nanofiltration membrane
By using aqueous phase monomers with non-planar twisted structures and the reactivity of phenolic/alcoholic hydroxyl groups to regulate interfacial polymerization, a high-porosity polyester loose selective layer is formed, which solves the problem of selecting existing nanofiltration membranes when improving permeability. Solve the problem of reduced performance and realize the preparation of nanofiltration membranes with high separation performance.
Patent Information
- Application Number
- CN202411640720.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
AI Technical Summary
Existing polyester loose nanofiltration membranes are difficult to maintain high selectivity when improving permeability, especially when entrapment of target substances such as Na2SO4 while increasing the permeability rate of water or other solvents.
Using aqueous phase monomers with non-planar twisted structures, the cross-linking degree of the interfacial polymerization reaction is controlled through the different reactivity of phenolic hydroxyl groups and alcoholic hydroxyl groups, and the cross-linking degree of the polyester separation layer is increased through heat treatment, thereby forming a high porosity, High surface area loose polyester selection layer.
While maintaining a high NA2SO4 cutting rate, it improves the penetration flux of polyester loose nanoic filter membranes, and is suitable for resource recovery and special separation of resource recovery and special separation in emerging fields.
Smart Images

Figure CN119345924A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanofiltration membrane preparation, and in particular to a method for preparing a polyester loose nanofiltration membrane. Background Art
[0002] In today's society, the importance of water resources is self-evident. With the global population growth, accelerated industrialization and rapid urbanization, water pollution is becoming increasingly serious, and available clean water resources are becoming increasingly scarce. People's requirements for water quality are constantly increasing, and more efficient and accurate water treatment technologies are needed in various fields, from domestic water to industrial water. Traditional water treatment methods, such as sedimentation, filtration, disinfection, etc., have gradually revealed their limitations in dealing with complex water quality problems. In the process of continuous development of membrane separation technology and exploration of new membrane materials, polyester loose nanofiltration membrane has become a research hotspot. Researchers are committed to developing polyester loose nanofiltration membranes with higher flux, higher selectivity, stronger stability and controllable cost. On the one hand, it is hoped that the performance of polyester membranes can be improved by improving the preparation process and other means, so that they can meet the complex water treatment needs in different fields; on the other hand, the application possibilities of polyester loose nanofiltration membranes in emerging fields such as resource recovery and special separation are explored to provide new technical support for solving resource and environmental problems.
[0003] At present, the preparation methods of polyester loose nanofiltration membranes mainly include phase inversion, co-deposition, layer-by-layer self-assembly, and interfacial polymerization. Among them, interfacial polymerization is the mainstream technology for the industrial preparation and laboratory research of nanofiltration membranes. The structure and functional groups of the monomers play a decisive role in the separation performance of loose nanofiltration membranes prepared by interfacial polymerization. During the research and development process, increasing the permeability of the membrane often leads to reduced selectivity, and vice versa. How to maximize the permeation rate of water or other solvents while ensuring good retention of the target substance is a key challenge. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a method for preparing a polyester loose nanofiltration membrane. The polyester loose nanofiltration membrane prepared by the present invention has a high permeation flux while maintaining a high Na2SO4 retention rate.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is a method for preparing a polyester loose nanofiltration membrane, comprising the following steps:
[0007] dissolving the aqueous phase monomer in a sodium hydroxide solution to obtain a NaOH solution containing the aqueous phase monomer;
[0008] Soaking the ultrafiltration membrane in the NaOH solution containing the aqueous phase monomer to obtain an ultrafiltration membrane support layer;
[0009] The ultrafiltration membrane support layer is contacted with a trimesoyl chloride solution to perform an interfacial polymerization reaction to obtain a primary nanofiltration membrane;
[0010] The primary nanofiltration membrane is subjected to heat treatment to obtain the polyester loose nanofiltration membrane;
[0011] The water phase monomer is a compound having a non-planar twisted structure and containing both a phenolic hydroxyl group and an alcoholic hydroxyl group.
[0012] The second technical solution of the present invention is a polyester loose nanofiltration membrane prepared by the above preparation method.
[0013] The present invention discloses the following technical effects:
[0014] The aqueous phase monomer selected by the present invention has a non-planar twisted structure and contains a compound of phenolic hydroxyl group and alcoholic hydroxyl group at the same time. The different reactivity of the phenolic hydroxyl group and the alcoholic hydroxyl group is utilized to change the reaction rate with trimesoyl chloride, thereby effectively regulating the cross-linking degree of oil / water interface polymerization. In addition, the non-planar twisted structure is conducive to the three-dimensional stacking of cross-linked molecular chains, thereby realizing the preparation of a polyester selection layer with high porosity, high specific surface area and looseness, thereby obtaining a nanofiltration membrane with high-efficiency separation performance.
[0015] The method provided by the invention is simple and easy to implement, has low required cost, and is conducive to realizing large-scale industrial production of high-efficiency nanofiltration membranes.
[0016] The polyester loose nanofiltration membrane prepared by the present invention has a higher permeation flux and can maintain a higher Na2SO4 retention rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 Fourier-total reflection infrared spectra of nanofiltration membranes M1, M2, M3, M4 and M5 of Examples 2-6;
[0019] Figure 2 The membrane surfaces of the nanofiltration membranes M1, M2, M3, M4 and M5 of Examples 2-6 are scanning electron microscope images;
[0020] Figure 3 is the contact angle of the nanofiltration membranes M1, M2, M3, M4 and M5 of Examples 2-6;
[0021] Figure 4The Na2SO4 permeation flux and rejection rate of the nanofiltration membranes M1, M2, M3, M4 and M5 of Examples 2-6;
[0022] Figure 5 The permeation flux and retention rate of the nanofiltration membrane M3 of Example 4 for four inorganic salts (NaCl, MgSO4, CaCl2, MgCl2). DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0028] The present invention provides a method for preparing a polyester loose nanofiltration membrane, comprising the following steps:
[0029] dissolving the aqueous phase monomer in a sodium hydroxide solution to obtain a NaOH solution containing the aqueous phase monomer;
[0030] Soaking the ultrafiltration membrane in the NaOH solution containing the aqueous phase monomer to obtain an ultrafiltration membrane support layer;
[0031] The ultrafiltration membrane support layer is contacted with a trimesoyl chloride solution to perform an interfacial polymerization reaction to obtain a primary nanofiltration membrane; the primary nanofiltration membrane comprises an ultrafiltration membrane support layer and a polyester separation layer;
[0032] The primary nanofiltration membrane is subjected to heat treatment to obtain the polyester loose nanofiltration membrane;
[0033] The water phase monomer is a compound having a non-planar twisted structure and containing both a phenolic hydroxyl group and an alcoholic hydroxyl group.
[0034] The present invention has no special requirements for the selection of ultrafiltration membranes. Commercially available ultrafiltration membranes well known to those skilled in the art may be selected, for example, commercially available flat ultrafiltration membranes (MWCO=20,000) supported by non-woven fabrics.
[0035] In some embodiments of the present invention, the aqueous phase monomer is phlorizin, 3-hydroxyphlorizin, 4,4-deoxyphlorizin, linalool, naringin dihydrochalcone, hesperidin dihydrochalcone glucoside, phlorizin-2'-O-glucuronide, trilobatin 2"-acetate, trilobatin, neohesperidin dihydrochalcone or 2',4',6'-trihydroxydihydrochalcone 4'-O-glucuronide, and the structural formula is shown in the following AK. The mass concentration of the aqueous phase monomer in the NaOH solution containing the aqueous phase monomer is 0.001-10.0%, preferably 0.1-5%, and more preferably 1-2%. The present invention has no special requirements for the way in which the aqueous phase monomer is dissolved in the sodium hydroxide solution, and the technical means well known to those skilled in the art can be used, such as stirring mixed dissolution and ultrasonic mixed dissolution.
[0036]
[0037] In the present invention, too high a concentration of aqueous monomers will cause the separation layer to be too thick and dense, resulting in a significant decrease in permeation flux and reduced separation efficiency of the nanofiltration membrane. In order to ensure the separation efficiency of the nanofiltration membrane, the present invention preferably sets the concentration of aqueous monomers within the above parameter range.
[0038] In some embodiments of the present invention, the mass concentration of the NaOH solution is 0.001-10.0%, preferably 0.01-5%, and more preferably 0.3-1.2%.
[0039] In the present invention, sodium hydroxide can promote the dissolution of aqueous phase monomers in water, and promote the reaction of aqueous phase monomers with trimesoyl chloride. As the concentration of the NaOH solution increases, the flux of the resulting polyester loose nanofiltration membrane increases, but the retention rate decreases. In order to make the polyester loose nanofiltration membrane have both high flux and retention rate, the present invention is preferably within the above parameter range.
[0040] In some embodiments of the present invention, the soaking time is 0.01-12 hours, preferably 0.25-3 hours, and more preferably 0.5-1 hour. The present invention has no special requirements on the volume of the aqueous phase monomer NaOH solution used for soaking the ultrafiltration membrane, as long as the ultrafiltration membrane is completely immersed.
[0041] In some embodiments of the present invention, after the soaking is completed, the step of taking out the ultrafiltration membrane support layer to which the monomer aqueous solution is attached and wiping the surface thereof to remove water droplets on the surface is also included.
[0042] In some embodiments of the present invention, the mass concentration of the trimesoyl chloride solution is 0.001-0.3%, preferably 0.05-0.15%, and more preferably 0.1-0.15%.
[0043] In some embodiments of the present invention, the ultrafiltration membrane support layer is contacted with the trimesoyl chloride solution by dripping the trimesoyl chloride solution onto the surface of the ultrafiltration membrane support layer at a dripping rate of 1 mL / s. In the present invention, the solvent of the trimesoyl chloride solution is n-hexane.
[0044] In some embodiments of the present invention, the interfacial polymerization reaction time is 0.1-600 min, preferably 1-100 min, more preferably 5-10 min. Through the interfacial polymerization reaction between the aqueous phase monomer molecules and trimesoyl chloride, a polyester loose separation layer is formed on the surface of the ultrafiltration membrane support layer.
[0045] In some embodiments of the present invention, the temperature of the heat treatment is 20-90°C (preferably 40-70°C), and the time is 0.01-12.0h (preferably 0.1-2h). In the present invention, the heat treatment is preferably carried out in an oven. The present invention is beneficial to improving the crosslinking degree of the polyester separation layer formed by interfacial polymerization through heat treatment. If the heat treatment temperature is too high, on the one hand, it will cause the crosslinking density of the separation layer to be too high, the permeation flux will decrease, and the separation efficiency will decrease. On the other hand, it will also affect the structure and performance of the ultrafiltration membrane of the supporting layer. In order to ensure better permeation flux and separation efficiency, the parameters of the preferred heat treatment of the present invention are within the above range.
[0046] In some embodiments of the present invention, after the heat treatment is completed, a soaking step in water is further included; the soaking time is 0.5-30 days. The present invention can remove the reactive monomer molecules that may be attached to the support layer by soaking in water.
[0047] The present invention creatively adopts a water-phase monomer with a non-planar twisted structure. The three-dimensional stacking of cross-linked molecular chains can significantly increase the specific surface area and porosity of the polyester selective layer. At the same time, the different reactivity of phenolic hydroxyl groups and alcoholic hydroxyl groups can effectively regulate the degree of cross-linking of the separation layer. The above multiple factors work together to help form a looser polyester loose separation layer, which maximizes the permeation flux of the nanofiltration membrane while retaining good solute selective separation performance. Furthermore, the present invention optimizes the structural parameters of the polyester separation layer by regulating the type of molecules with a non-planar twisted structure and containing phenolic hydroxyl groups and alcoholic hydroxyl groups, the heat treatment time, temperature, and the concentration of the reaction monomer and the concentration of NaOH, ensuring that high permeation flux is obtained while maintaining excellent solute selective separation performance. The implementation results show that the permeation flux of the nanofiltration membrane obtained by the method of the present invention can reach 70.32L·m -2 ·h -1 bar -1 The retention rate of Na2SO4 is 84.21%.
[0048] The present invention also provides a polyester loose nanofiltration membrane prepared by the above preparation method. In the polyester loose nanofiltration membrane prepared by the present invention, the thickness of the polyester separation layer is 5 to 200 nm, and the effective area is 1 to 50 cm 2 .
[0049] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0050] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0051] Example 1
[0052] A commercial flat ultrafiltration membrane (MWCO=20000) supported by non-woven fabric (which can be cut into appropriate sizes as needed) is recorded as flat ultrafiltration membrane support layer M0, and then immersed in deionized water for testing and the next step of modification.
[0053] Example 2
[0054] Step 1. dissolving phlorizin in a 0.3 wt % NaOH aqueous solution, wherein the concentration of phlorizin in the obtained NaOH solution containing phlorizin is 1.0 wt %, and a total of 100 mL is prepared;
[0055] Step 2. Soak the flat ultrafiltration membrane support layer M0 in Example 1 in a NaOH solution containing phlorizin for 30 minutes, then take it out and wipe off the excess aqueous solution on its surface until there are no obvious water drops, to obtain an ultrafiltration membrane support layer;
[0056] Step 3. Prepare 100 mL of a 0.1% mass concentration of trimesoyl chloride solution (solvent is n-hexane), drop the trimesoyl chloride solution onto the surface of the ultrafiltration membrane support layer (dropping rate is 1 mL / s) for 5 minutes of interfacial polymerization to obtain a primary nanofiltration membrane;
[0057] Step 4. The primary nanofiltration membrane was placed in an oven at 60° C. for 0.5 h, and then immersed in deionized water for 12.0 h to obtain a polyester loose nanofiltration membrane, which was recorded as nanofiltration membrane M1.
[0058] Example 3
[0059] The same as Example 2, the only difference is that the concentration of NaOH is adjusted to 0.5wt%, and the other operations are the same to obtain a nanofiltration membrane M2.
[0060] Example 4
[0061] The same as Example 2, the only difference is that the concentration of NaOH is adjusted to 0.8wt%, and the other operations are the same to obtain a nanofiltration membrane M3.
[0062] Example 5
[0063] The same as Example 2, the only difference is that the concentration of NaOH is adjusted to 1.0wt%, and the other operations are the same to obtain a nanofiltration membrane M4.
[0064] Example 6
[0065] The same as Example 2, the only difference is that the concentration of NaOH is adjusted to 1.2 wt %, and the other operations are the same to obtain a nanofiltration membrane M5.
[0066] The Fourier-total reflection infrared spectra of the surfaces of nanofiltration membranes M1-M5 are shown in Figure 1 As shown in the figure, it can be seen that at 1731cm -1 The characteristic absorption peak of OC=O of ester bond appears nearby, thus proving the successful preparation of polyester layer separation layer.
[0067] Scanning electron microscopy images of the membrane surfaces of nanofiltration membranes M1-M5 are shown in Figure 2 As shown in the figure, it can be seen that with the increase of NaOH content, defects of various sizes gradually appear on the surface of the polyester layer. This is mainly because the addition of excessive NaOH hydrolyzes the polyester layer, which may lead to a decrease in the degree of crosslinking and a decrease in the average pore size.
[0068] The water contact angles of nanofiltration membranes M1-M5 are as follows Figure 3 As shown in the figure, with the increase of NaOH content, the hydrophilicity of the membrane continues to increase, which is one of the reasons why the permeation flux is improved.
[0069] Example 7
[0070] The same as Example 4, the only difference is that phlorizin is replaced by 3-hydroxyphlorizin, and the other operations are the same to obtain nanofiltration membrane M6.
[0071] Example 8
[0072] The same as Example 4, the only difference is that phlorizin is replaced by 4,4-deoxyphlorizin, and the other operations are the same to obtain nanofiltration membrane M7.
[0073] Example 9
[0074] The same as Example 4, the only difference is that phlorizin is replaced by lignin, and the other operations are the same to obtain nanofiltration membrane M8.
[0075] Example 10
[0076] The same as Example 4, the only difference is that naringin dihydrochalcone is used to replace phlorizin, and the other operations are the same to obtain nanofiltration membrane M9.
[0077] Embodiment 11
[0078] The same as Example 4, the only difference is that phlorizin is replaced by hesperetin dihydrochalcone glucoside, and the other operations are the same to obtain nanofiltration membrane M10.
[0079] Example 12
[0080] The same as Example 4, the only difference is that phlorizin is replaced by phlorizin-2'-O-glucuronide, and the other operations are the same to obtain nanofiltration membrane M11.
[0081] Embodiment 13
[0082] The same as Example 4, the only difference is that phlorizin is replaced by trilobatin 2"-acetate, and the other operations are the same to obtain nanofiltration membrane M12.
[0083] Embodiment 14
[0084] The same as Example 4, the only difference is that phlorizin is replaced by trilobatin, and the other operations are the same to obtain nanofiltration membrane M13.
[0085] Embodiment 15
[0086] The same as Example 4, the only difference is that phlorizin is replaced by neohesperidin dihydrochalcone, and the other operations are the same to obtain nanofiltration membrane M14.
[0087] Performance Testing
[0088] (I) The permeability of nanofiltration membranes M1, M2, M3, M4 and M5 was tested using cross-flow medium and low pressure filtration equipment, and their permeation flux and retention rate for five inorganic salt solutions (1.0 g / L, Na2SO4, NaCl, MgSO4, CaCl2, MgCl2) were calculated as follows:
[0089] The membrane to be tested was pre-pressed at 0.4 MPa for 30 min, and then the pressure was reduced to 0.2 MPa. The five salt solutions were tested for 1 h, and the permeation volume (L) was recorded.
[0090] The permeation flux J was calculated according to formula 1:
[0091] In formula 1, J is the permeation flux, L / m 2 ·h; V is the permeation volume, L; A is the effective permeation area of the nanofiltration membrane, m 2 ; t is the penetration time, h; ΔP is the operating pressure, bar.
[0092] The solute retention rate R is calculated according to formula 2:
[0093] In formula 2, R is the interception rate, %; C p is the permeate concentration; C f is the feed solution concentration.
[0094] After testing, the pure water permeation flux and Na2SO4 retention rate of M1, M2, M3, M4 and M5 are shown in Table 1 and Figure 4 .
[0095] Table 1 Permeation flux and Na2SO4 retention rate of M1, M2, M3, M4 and M5
[0096] Membrane Type <![CDATA[Permeation flux (L·m -2 h -1 ·bar -1 )]]> Retention rate (%) M1 4.59 96.23 M2 7.03 91.36 M3 70.32 84.21 M4 89.43 56.85 M5 141.41 39.21
[0097] As shown in Table 1, as the mass concentration of NaOH solution increases to 1.2wt%, the permeation flux of nanofiltration membranes M1 to M5 gradually increases while the retention rate of Na2SO4 decreases. This is mainly due to the increase in NaOH concentration, the hydrolysis of ester bonds by -OH, which affects the cross-linking degree of the membrane. In addition, the use of non-planar twisted structure water phase monomers and the three-dimensional stacking of molecules can significantly increase the specific surface area and porosity of the polyester separation layer. At the same time, the different reactivity of phenolic hydroxyl and alcoholic hydroxyl can effectively regulate the cross-linking degree of the separation layer. The above multiple factors work together to help form a looser polyester loose selection layer, which maximizes the permeation flux of the nanofiltration membrane while retaining good selective separation performance. For example, the permeation flux of M3 can reach 70.32L·m -2 ·h -1 bar -1The Na2SO4 retention rate can reach 84.21%.
[0098] The present invention also tested the pure water permeation flux and the retention rate of Na2SO4 of the nanofiltration membrane M6-M14. The pure water permeation flux and the retention rate of Na2SO4 were similar to those of M3, and the pure water permeation flux reached 70L·m -2 h -1 bar -1 The above results show that the retention rate of Na2SO4 is over 80%.
[0099] (II) The above method was used to test the permeation flux and solute retention rate of M3 for four inorganic salt solutions (NaCl, MgSO4, CaCl2, MgCl2). The results are shown in Table 2 and Figure 5 shown.
[0100] Table 2 Permeation flux and solute retention rate of M3 for the other four salts (NaCl, MgSO4, CaCl2, MgCl2)
[0101] Inorganic salt types <![CDATA[Permeation flux (L·m -2 h -1 ·bar -1 )]]> Retention rate (%) NaCl 62.68 20.51 <![CDATA[MgSO4]]> 26.75 25.33 <![CDATA[CaCl2]]> 37.45 8.76 <![CDATA[MgCl2]]> 26.29 9.40
[0102] It can be seen from Table 2 that the nanofiltration membrane M3 has a low retention rate for the above four inorganic salts, which is mainly related to the fact that the retention of solutes by the nanofiltration membrane is affected by the combined influence of the Donan effect and the pore size screening theory. 2+ , Ca 2+ Positively charged, easily adsorbed on the negatively charged polyester separation layer, while Cl - It is a monovalent negative ion with a smaller ion size, so compared with Na2SO4, MgSO4, NaCl, CaCl2 and MgCl2 are easier to pass through the nanofiltration membrane, and the retention rate is relatively low.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a polyester loose nanofiltration membrane, characterized in that: The following steps are involved: dissolving the aqueous phase monomer in a sodium hydroxide solution to obtain a NaOH solution containing the aqueous phase monomer; Soaking the ultrafiltration membrane in the NaOH solution containing the aqueous phase monomer to obtain an ultrafiltration membrane support layer; The ultrafiltration membrane support layer is contacted with a trimesoyl chloride solution to perform an interfacial polymerization reaction to obtain a primary nanofiltration membrane; The primary nanofiltration membrane is subjected to heat treatment to obtain the polyester loose nanofiltration membrane; The water phase monomer is a compound having a non-planar twisted structure and containing both a phenolic hydroxyl group and an alcoholic hydroxyl group.
2. The method for preparing a polyester loose nanofiltration membrane according to claim 1, characterized in that: The aqueous phase monomer is phlorizin, 3-hydroxyphlorizin, 4,4-deoxyphlorizin, linalool, naringin dihydrochalcone, hesperidin dihydrochalcone glucoside, phlorizin-2'-O-glucuronide, trilobatin 2"-acetate, trilobatin, neohesperidin dihydrochalcone or 2',4',6'-trihydroxydihydrochalcone 4'-O-glucuronide; the mass concentration of the aqueous phase monomer in the NaOH solution containing the aqueous phase monomer is 0.001-10.0%.
3. The method for preparing a polyester loose nanofiltration membrane according to claim 1, characterized in that: The mass concentration of the NaOH solution is 0.001-10.0%.
4. The method for preparing a polyester loose nanofiltration membrane according to claim 1, characterized in that: The soaking time is 0.01-12h.
5. The method for preparing a polyester loose nanofiltration membrane according to claim 1, characterized in that: The mass concentration of the trimesoyl chloride solution is 0.001-0.3%.
6. The method for preparing a polyester loose nanofiltration membrane according to claim 1, characterized in that: The interfacial polymerization reaction time is 0.1 to 600 minutes.
7. The method for preparing a polyester loose nanofiltration membrane according to claim 1, characterized in that: The heat treatment temperature is 20-90° C. and the time is 0.01-12.0 h.
8. The method for preparing a polyester loose nanofiltration membrane according to claim 1, characterized in that: After the heat treatment is completed, the step of soaking in water is also included; the soaking time is 0.5-30 days.
9. A polyester loose nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing nanofiltration membrane by electrostatic spraying and product thereof
CN108201790A
Aliphatic polyamide loose reverse osmosis membrane as well as preparation method and application thereof
CN108246128A
Tannic acid-hydroxypropyl beta cyclodextrin composite nanofiltration membrane and preparation method thereof
CN113457468A
Preparation method of high-interception antibacterial nanofiltration membrane based on naringin
CN116236932A
Composite nanofiltration membrane as well as preparation method and application thereof
CN117323846A
Cited By
Alkali-resistant polyester loose nanofiltration membrane based on 2, 2, 4, 4-tetramethyl-1, 3-cyclobutanediol as well as preparation method and application of alkali-resistant polyester loose nanofiltration membrane
CN120550639A
Alkali-resistant polyester loose nanofiltration membrane based on 2,2,4,4-tetramethyl-1,3-cyclobutanediol and preparation method and application thereof
CN120550639B
Thin-layer composite ultrafiltration membrane as well as preparation method and application thereof
CN120571430A
Hesperidin-regulated polyamide nanofiltration membrane as well as preparation method and application thereof
CN120900446A
Hesperidin-regulated polyamide nanofiltration membrane, preparation method and application thereof
CN120900446B